Castration causes an increase in lysosomal size and upregulation of cathepsin D expression in principal cells along with increased secretion of procathepsin D and prosaposin oligomers in adult rat epididymis - Carvelli, Flavia Lorena (2021)
In the epididymis, lysosomal proteins of the epithelial cells are normally targeted from the Golgi apparatus to lysosomes for degradation, although their secretion into the epididymal lumen has been documented and associated with sperm maturation. In this study, cathepsin D (CatD) and prosaposin (PSAP) were examined in adult epididymis of control, and 2-day castrated rats without (Ct) and with testosterone replacement (Ct+T) to evaluate their expression and regulation within epididymal epithelial cells. By light microscope-immunocytochemistry, a quantitative increase in size of lysosomes in principal cells of Ct animals was noted from the distal initial segment to the proximal cauda. Androgen replacement did not restore the size of lysosomes to control levels. Western blot analysis revealed a significant increase in CatD expression in the epididymis of Ct animals, which suggested an upregulation of its expression in principal cells; androgens restored levels of CatD to that of controls. In contrast, PSAP expression in Ct animals was not altered from controls. Additionally, an increase in procathepsin D levels was noted from samples of the epididymal fluid of Ct compared to control animals, accompanied by an increased complex formation with PSAP. Moreover, an increased oligomerization of prosaposin was observed in the epididymal lumen of Ct rats, with changes reverted to controls in Ct+T animals. Taken together these data suggest castration causes an increased uptake of substrates that are acted upon by CatD in lysosomes of principal cells and in the lumen by procathepsin D. These substrates may be derived from apoptotic cells noted in the lumen of proximal regions and possibly by degenerating sperm in distal regions of the epididymis of Ct animals. Exploring the mechanisms by which lysosomal enzymes are synthesized and secreted by the epididymis may help resolve some of the issues originating from epididymal dysfunctions with relevance to sperm maturation.